2020
DOI: 10.1029/2019jb019164
|View full text |Cite
|
Sign up to set email alerts
|

Slab Rollback Versus Delamination: Contrasting Fates of Flat‐Slab Subduction and Implications for South China Evolution in the Mesozoic

Abstract: Growing evidence supports that the widely developed Mesozoic folds and magmatism in the South China Block are attributed to the flat-slab subduction, followed by slab steepening, of the Paleo-Pacific Plate (PPP). However, the dynamics of the transition from flatto steep-slab subduction, as well as the relationship between tectonic processes and surface deformation and magmatic events, are poorly constrained. Using a 2-D thermomechanical numerical model, we systematically investigate the effects of slab rollbac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 74 publications
(143 reference statements)
3
38
0
Order By: Relevance
“…Thus, we propose this anomaly to be a fossil fragment of the Nazca slab that was subducting steeply prior to the onset of flattening, indicating break-off from the leading edge of the current Nazca slab (Liu & Currie, 2016). Slab break-off during the slab flattening process is common in geodynamic models (e.g., Dai et al, 2020;Haschke et al, 2002;Liu & Currie, 2016. The conditions for slab break-off during the slab flattening process include fast trenchward migration of the overriding plate (high convergence rate) and a strong buoyancy contrast between either an oceanic plateau or aseismic ridge crust (here the JFR) and the normal thickness oceanic crust of an old slab (Haschke et al, 2002;Li et al, 2011;Liu & Currie, 2016.…”
Section: Slab Break-off: Transition From Steep To Flat Subduction?mentioning
confidence: 89%
“…Thus, we propose this anomaly to be a fossil fragment of the Nazca slab that was subducting steeply prior to the onset of flattening, indicating break-off from the leading edge of the current Nazca slab (Liu & Currie, 2016). Slab break-off during the slab flattening process is common in geodynamic models (e.g., Dai et al, 2020;Haschke et al, 2002;Liu & Currie, 2016. The conditions for slab break-off during the slab flattening process include fast trenchward migration of the overriding plate (high convergence rate) and a strong buoyancy contrast between either an oceanic plateau or aseismic ridge crust (here the JFR) and the normal thickness oceanic crust of an old slab (Haschke et al, 2002;Li et al, 2011;Liu & Currie, 2016.…”
Section: Slab Break-off: Transition From Steep To Flat Subduction?mentioning
confidence: 89%
“…The SCB is characterized by widespread extensional basin and dome generation, voluminous magma intrusion, and associated polymetallic mineralization during the Cretaceous (Figures 1 and 5; Dai et al, 2020; Li, Zhang, et al, 2014; Wang & Shu, 2012). A comprehensive study of these data can help us reconstruct the Cretaceous tectonic evolution of the SCB.…”
Section: Discussionmentioning
confidence: 99%
“…The tectonic evolution of the South China Block (SCB) in the Cretaceous is characterized by widespread extensional basin and dome generation, voluminous magma intrusions and associated polymetallic mineralization (Figure 1; Deng, Wang, & Li, 2017; Deng & Wang, 2016; Li, Zhang, et al, 2014 and reference therein). Most researchers relate this process to the subduction of the Pacific Plate (e.g., Dai et al, 2020; Deng, Zhang, Fan, & Pérez‐Gussinyé, 2014; Li, Jiang, Zhang, Zhao, & Zhao, 2015; Li & Li, 2007; Pan et al, 2018; Shi, Dong, Zhang, & Huang, 2015; Wang, Fan, Zhang, & Zhang, 2013; Wang & Shu, 2012; Xu, Deng, & O'Reilly, 2003; Zhou, Sun, Shen, Shu, & Niu, 2006). During the Cretaceous, the subduction of the Pacific Plate changed the intracontinental topography, and various fission track (FT) thermochronological investigations of the apatite and zircon have indicated that the southwestern SCB experienced an intricate pattern of uplift and exhumation (Guo, 2004; Li, Wang, Tan, & Peng, 2005; Zhou, Gon, Shen, Xu, & Yang, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The oceanic mantle consists of 73 km of dry olivine (Hirth & Kohlstedt, 2004), and is compositionally lighter than the asthenosphere (ρAsthenosphere -20 kg/m³). The lithosphere is given an initial dip of ~15° to facilitate the initial flat slab stage (Van Hunen et al, 2004;Huangfu et al, 2016;Liu & Currie, 2016;Dai et al, 2020). A 12 km thick "ridge" (2800 kg/m³) of weak quartz (Ranalli, 1997) is placed along the dipping subduction interface to aid in subduction initialization.…”
Section: Methodsmentioning
confidence: 99%